2017
DOI: 10.1111/fwb.12880
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of habitat disturbance on adult and larval dragonflies (Odonata) in rainforest streams in Sabah, Malaysian Borneo

Abstract: SUMMARY1. Dragonfly assemblages (Odonata: comprising damselflies, Zygoptera; and dragonflies, Anisoptera) in Southeast Asian rainforests are extremely diverse but increasingly threatened by habitat disturbance, including logging and conversion of forest to oil palm plantations. 2. Land-use change can affect dragonfly larval stages by altering within-stream environmental conditions, and adults by loss of perches, shade and hunting habitat. However, the extent to which dragonflies are affected by land-use change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 57 publications
(80 reference statements)
6
60
1
2
Order By: Relevance
“…In contrast, for dung beetles, we found that for several species they were unable to penetrate the oil palm matrix and preferentially used the riparian reserves to move within the matrix landscape and between forests. Our findings have implications for setaside forest within oil palm landscapes and support the growing evidence base that contiguous riparian forest corridors are essential for maintaining biodiversity for many invertebrate taxa (Barlow et al, 2010, Gray et al 2016, Luke et al 2017, Scriven et al 2017. The copyright holder for this preprint (which was not .…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the supporting
confidence: 78%
“…In contrast, for dung beetles, we found that for several species they were unable to penetrate the oil palm matrix and preferentially used the riparian reserves to move within the matrix landscape and between forests. Our findings have implications for setaside forest within oil palm landscapes and support the growing evidence base that contiguous riparian forest corridors are essential for maintaining biodiversity for many invertebrate taxa (Barlow et al, 2010, Gray et al 2016, Luke et al 2017, Scriven et al 2017. The copyright holder for this preprint (which was not .…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the supporting
confidence: 78%
“…In oil palm plantations in Malaysia, the environmental integrity and diversity of aquatic biota are affected by soil conditions and land use within their drainage basins; thus, there is a need to include and manage riparian buffers in streams of oil palm areas (Mercer et al ., ; Luke et al ., 2017a). In Brazil, the Forest Code – Law 4.771/65 – determines that water bodies in plantation areas must maintain forested buffers, which are called Permanent Preservation Areas (PPAs).…”
Section: Introductionmentioning
confidence: 99%
“…Streams flowing through plantations and other cleared areas are warmer, shallower, have more sand and reduced abundance of species such as dragonflies (210,211), although flood-control channels can serve as habitat for some water birds in oil palm areas (212).…”
Section: Climate Changementioning
confidence: 99%
“…Fish and stream macroinvertebrates in protected streams are typically more similar in composition to those found in pristine forests than unprotected streams in farmland (210,344,345). For example, species that use leaf litter and coarse substrate for hiding and foraging were found to be missing from oil palm sites that did not have riparian reserves (345).…”
Section: Conservation Scopementioning
confidence: 99%